The influence of the Tanzimat and Jadidism on the enlightenment of Alash (literary aspect) (Eurasian Journal of Philology Science and Education, 2024)
This article discusses the era of the awakening of the Turkic world, its enlightenment, culture, and educational sphere. In the first half of the XIX century in the Ottoman Empire (Turkey), which began to fall into economic and cultural decline, there was a revolution of "Tanzimatists". They have carried out a "new reform" that will completely change Turkey's system of government, culture, religious trends, and social status. The "new reform" prevailed by the nature of the enlightenment. As a result, new schools and educational institutions were opened in Turkey, and newspapers, magazines, and books by Turkish poets and writers were published, as a result of which the cultural and social potential of the population grew.The "Awakening period" that began among the Turkish people significantly impacted the Crimean and Kazan Tatars among Russian Muslims. The immediate motive was the Crimean Tatar scientist, politician, and journalist I. Gasprali. The name of I. Gasprali is immortalized in history by introducing the "Jadit" method into the cult of the Turkic peoples. Revolutionaries who violated the established principle and supported a new method of teaching focused on Western civilization were called "jaditists".At the beginning of the XX century, the Jadit movement, in turn, reached the Kazakh land among the Muslims of Russia. This "new wave", the internal content of which is very similar to the "Jadit" movement, was named in Kazakhstan – the "Alash" movement. The founders of the Alash movement were Alash intellectuals led by the politician-scientist A. Bokeikhan. The Alash intelligentsia has made an outstanding contribution to the culture of the Kazakh people, educational, scientific, and political activities, and preserving the modern Kazakh land as an independent state.Keywords: the Turkic world, the era of the Tanzimat, Tatar scientist, Jadidism, the Alash movement.